2023
DOI: 10.1177/19458924231177855
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recalcitrant Chronic Rhinosinusitis in Non-Solid and Solid Transplant Recipients

Abstract: Objectives Transplant patients are high risk for surgery due to their immunocompromised state. There is a paucity of evidence concerning the differences in incidence of chronic rhinosinusitis (CRS) in solid versus non-solid organ transplant. Our aim is to analyze the difference in incidence of CRS requiring endoscopic sinus surgery (ESS) between non-solid and solid transplant populations and determine if certain risk factors are associated with increased incidence of recalcitrant CRS in non-solid versus solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Retrospective analysis of patients chronic rhinosinusitis (CRS) with both solid and nonsolid organ transplants found an increased need for surgery and more recalcitrant disease. 6 The authors further identified specific factors, including certain immunotherapy medications, pancytopenia, and rejection, which correlate to the need for surgery, suggesting that this population warrants close monitoring.…”
mentioning
confidence: 98%
“…Retrospective analysis of patients chronic rhinosinusitis (CRS) with both solid and nonsolid organ transplants found an increased need for surgery and more recalcitrant disease. 6 The authors further identified specific factors, including certain immunotherapy medications, pancytopenia, and rejection, which correlate to the need for surgery, suggesting that this population warrants close monitoring.…”
mentioning
confidence: 98%